Tension-Pleasure and Education Values of the Meta-Figurative of Indonesian Contemporary Paintings - Adnyana, I Wayan Kun; Totton, Mary Louise; Remawa, Anak Agung Gede Rai; Muka, I Ketut; Ruta, I Made; Wirakesuma, I Nengah; Kondra, I Wayan; Suardana, I Wayan; Sugita, I Ketut Adi (Harmonia: Journal of Arts Research and Education, 2023)
Meta-figurative is a physical aesthetic discourse that reaches beyond the physical beauty of ideal bodies (skeletal construction, muscles, and skins). The interpretation approaches used new criticism, according to Culler (2001), that goal to identify what the works repress or illuminate by concealing and portraying society and social attitudes. Meta-figurative encompasses exploration pertaining to the interchangeable position and condition between tensions and pleasures of bodies in the social space. Fifteen Indonesian contemporary artists are: Mangu Putra, Entang Wiharso, Chusin Setiadikara, Agus Suwage, FX Harsono, Ivan Sagito, Heri Dono, Ronald Manulang, Nyoman Masriadi, Nyoman Erawan, Putu Sutawijaya, Laksmi Sitaresmi, Made Djirna, Ugo Untoro, and Bob Sick Yuditha have been conducting creative efforts and questioning about matters of the bodies’ position in the public space, conducting current interpretation through personal artistic and aesthetical language. There are five representation tendencies of meta-figurative paintings thematically, artistic images, and visual meanings: marginalized bodies, fictionalized bodies, bodies of expression, autobiographical bodies, and beyond famous portraits. Indonesian contemporary artists have made figurative subjects in their paintings to make statements, self-reflections, and moral voices of their country’s socio-political conditions, which are educational values of Indonesian Contemporary Paintings in social meaning. Poverty, corruption, and anti-democracy practices still part of Indonesian daily realities are area protests for contemporary artists.